# Step-by-step Solution

## Solve the differential equation $dx+e^{3x}dy=0$

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$y=\frac{1}{3e^{3x}}+C_0$

## Step-by-step Solution

Problem to solve:

$dx+e^{3x}dy=0$

Choose the solving method

1

We need to isolate the dependent variable $y$, we can do that by subtracting $dx$ from both sides of the equation

$e^{3x}dy=-dx$

Learn how to solve differential equations problems step by step online.

$e^{3x}dy=-dx$

Learn how to solve differential equations problems step by step online. Solve the differential equation dx+e^(3x)dy=0. We need to isolate the dependent variable y, we can do that by subtracting dx from both sides of the equation. Group the terms of the differential equation. Move the terms of the y variable to the left side, and the terms of the x variable to the right side of the equality. Integrate both sides of the differential equation, the left side with respect to y, and the right side with respect to x. Solve the integral \int1dy and replace the result in the differential equation.

$y=\frac{1}{3e^{3x}}+C_0$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$dx+e^{3x}dy=0$